Proceedings of the 8th Conference on Human-Computer Interaction With Mobile Devices and Services 2006
DOI: 10.1145/1152215.1152238
|View full text |Cite
|
Sign up to set email alerts
|

Comparing conceptual designs for mobile access to geo-spatial information

Abstract: Spatial information appliances (SIA), which enable mobile users to interact with the physical environment, have recently received an increasing amount of interest from the research community. This paper presents a comparative outdoor user study on conceptual designs for 4 interaction areas considered important for SIAs: selection, search, information sniffing, and remote viewing. Implications for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…Previous empirical research has partly substantiated this hypothesis, at least for indoor navigation [9] . Our comparative user study with a Wizard-of-Oz prototype showed that POIs are much easier accessible with orientation-aware displays than with a standard static version [6] .…”
Section: Design Dimensions Of Msi Applicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous empirical research has partly substantiated this hypothesis, at least for indoor navigation [9] . Our comparative user study with a Wizard-of-Oz prototype showed that POIs are much easier accessible with orientation-aware displays than with a standard static version [6] .…”
Section: Design Dimensions Of Msi Applicationsmentioning
confidence: 93%
“…Information that is related to objects, geographical features or buildings that are visible to the user may be contextually more relevant than information about objects that are not. Interactive, ego-centric maps on mobile devices provide added value if they contain indications of the visibility of surrounding features, as has been shown by [6] Visibility information enables entirely new interaction metaphors on mobile devices equipped with advanced sensors such as GPS and digital compass, as has been described by [2] and [15] .…”
Section: The Local Visibility Modelmentioning
confidence: 99%
“…In Gardiner 2004;Chan et al 2005;Fröhlich et al 2006;Fröhlich 2007a, 2007b;Simon, Fröhlich, and Grechenig 2008;Gardiner, Yin, and Carswell 2009;Carswell, Gardiner and Yin 2010a), the idea of an egocentric view of the world is investigated in a mobile context. In , the idea of using a triangular 2D shape to represent a user's field-of-view (FOv) to query POIs stored in a spatial database was introduced.…”
Section: Mobile Spatial Interactionmentioning
confidence: 99%
“…Google Earth has been explored for AR/MR related applications to give "remote viewing" of geo-spatial information (Fröhlich et al, 2006) and urban planning (Phan & Choo, 2010). Keyhole Markup Language (KML) files used in Google Earth have been used for defining the augmented object and its placement (Honkamaa, 2007).…”
Section: Related Workmentioning
confidence: 99%